2022
DOI: 10.1002/ente.202200938
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Recycling of Spent Ionic Liquid Dual‐Ion Batteries

Abstract: Ionic liquid (IL) dual‐ion batteries (DIBs) are widely studied as advanced electrochemical systems because of their potential nonflammability, environmental friendliness, and high working voltage. Recycling and reusing valuable IL electrolytes and metallic Ni current collectors might boost the application of IL DIBs. Herein, the preliminary results of the recycling of a spent DIB with 1,2‐dimethyl‐3‐propylimidazolium chloroaluminate (DMPI+)(AlCl4−) electrolyte are reported. Recovery rates of most components (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…However, there is limited research on DIBs using organic moieties of imidazolium (1-ethyl-3-methyl imidazolium and 2,3-dimethyl-1-propyl imidazolium) and pyrrolidinium-based (N-butyl-Nmethyl pyrrolidinium) cations in the graphite anode. 30,32 Exploring DIBs with other organic moieties-based cations, like morpholium, piperidinium, and thiazolium, is challenging both computationally and experimentally due to the complexities of the ion intercalation process and the sensitivity of ILs. The intercalation of ions into the graphite electrode follows a proper staging mechanism, making computational studies time-consuming and costly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is limited research on DIBs using organic moieties of imidazolium (1-ethyl-3-methyl imidazolium and 2,3-dimethyl-1-propyl imidazolium) and pyrrolidinium-based (N-butyl-Nmethyl pyrrolidinium) cations in the graphite anode. 30,32 Exploring DIBs with other organic moieties-based cations, like morpholium, piperidinium, and thiazolium, is challenging both computationally and experimentally due to the complexities of the ion intercalation process and the sensitivity of ILs. The intercalation of ions into the graphite electrode follows a proper staging mechanism, making computational studies time-consuming and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the organic moieties of imidazolium and pyrrolidinium-based cations and counteranions such as OTf (CF 3 SO 3 ), AlCl 4 , PF 6 , and BF 4 of ILs are intercalated into the graphite anode and cathode, respectively, during the charging process. These DIBs show the higher cutoff changing voltage of 4.0–5.0 V, due to the broad electrochemical window of ILs. However, there is limited research on DIBs using organic moieties of imidazolium (1-ethyl-3-methyl imidazolium and 2,3-dimethyl-1-propyl imidazolium) and pyrrolidinium-based ( N -butyl- N -methyl pyrrolidinium) cations in the graphite anode. , Exploring DIBs with other organic moieties-based cations, like morpholium, piperidinium, and thiazolium, is challenging both computationally and experimentally due to the complexities of the ion intercalation process and the sensitivity of ILs. The intercalation of ions into the graphite electrode follows a proper staging mechanism, making computational studies time-consuming and costly.…”
Section: Introductionmentioning
confidence: 99%
“…31,32,35 However, only a few reports are exclusively found on utilizing regenerated graphite as an anion-storing cathode material. [36][37][38][39][40][41][42] Therefore, this study investigates the electrochemical compatibility of the regenerated graphite as both the cathode and anode. Finally, a graphite-based dual-ion full cell is fabricated, and its electrochemical performances are rigorously optimized toward developing a practical prototype.…”
Section: Introductionmentioning
confidence: 99%